2015
DOI: 10.1038/cmi.2015.01
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha blockage therapy impairs hepatitis B viral clearance and enhances T-cell exhaustion in a mouse model

Abstract: Hepatitis B virus (HBV) reactivation and recurrence are common in patients undergoing immunosuppression therapy. Tumor necrosis factor (TNF) blockage therapy is effective for the treatment of many autoimmune inflammatory diseases. However, the role of TNF-a blockage therapy in the innate and adaptive immune responses against HBV is still not clear. A detailed analysis of HBV infection under TNF-a blockage therapy is essential for the prophylaxis and therapy for HBV reactivation and recurrence. In this study, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…Furthermore, TNF-α blockade also abolishes the effects of TLR9 ligand-induced facilitation of HBV clearance. 1 Taken together, these results indicate that anti-TNF-α therapy impairs T cell functions and delays HBV clearance.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, TNF-α blockade also abolishes the effects of TLR9 ligand-induced facilitation of HBV clearance. 1 Taken together, these results indicate that anti-TNF-α therapy impairs T cell functions and delays HBV clearance.…”
mentioning
confidence: 84%
“…However, in a recent paper in Cell Mol Immunol, Chyuan et al reported that under TNF-α blockade, HBV viral clearance was impaired with persistent elevated HBV viral load in a dose and temporal-dependent manner. 1 It demonstrates that a deficiency of TNF-α reduces viral clearance and promotes HBV persistence in a mouse model, and the impairment of HBV clearance under anti-TNF-α occurs at an early time point of HBV infection, suggesting that HBV may reactivate during therapy with TNF inhibitors. The results together with previous reports support that TNF is a key innate cytokine required to clear HBV.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…40 Studies that have antagonized TNF signaling during infection have shown that this treatment causes impairment in virological control, 38, 68 a reduction in Toll-like receptor 9 activation and T-cell exhaustion. 69 …”
Section: The Role Of Tnf In Hbvmentioning
confidence: 99%
“…40 Studies that have antagonized TNF signaling during infection have shown that this treatment causes impairment in virological control, 38,68 a reduction in Toll-like receptor 9 activation and T-cell exhaustion. 69 The cIAP proteins are critical decision makers in determining whether TNF promotes cellular activation and survival signaling or cell death. As discussed above, in the absence of cIAPs TNF-signaling causes cell death.…”
Section: The Role Of Tnf In Hbvmentioning
confidence: 99%